2019
DOI: 10.1016/j.ebiom.2019.09.051
|View full text |Cite
|
Sign up to set email alerts
|

circHIPK3 promotes oxaliplatin-resistance in colorectal cancer through autophagy by sponging miR-637

Abstract: BackgroundResistance to oxaliplatin-based chemotherapy is a major cause of recurrence in colorectal cancer (CRC) patients. There is increasing evidence indicating that circHIPK3 is involved in the development and progression of tumours. However, little is known about the potential role of circHIPK3 in CRC chemotherapy and its molecular mechanisms in chemoresistance also remain unclear.MethodsQuantitative real-time PCR was performed to detect circHIPK3 expression in tissues of 2 cohorts of CRC patients who rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 59 publications
1
73
0
Order By: Relevance
“…Our research showed that circHIPK3, which mainly existed in the cytoplasm, was high-expressed in RC tissues and cells, and that knocking down circHIPK3 could inhibit the proliferation, migration and invasion of RC cells. Previous reports revealed that circHIPK3 is highexpressed in the tissues and cells of colon carcinoma, non-small cell lung carcinoma, and nasopharyngeal carcinoma [25][26][27]. However, Li et al [28] found that circHIPK3 is significantly down-regulated in bladder carcinoma cells and is negatively related to the classification, invasion of bladder carcinoma and lymph node metastasis.…”
Section: Discussionmentioning
confidence: 96%
“…Our research showed that circHIPK3, which mainly existed in the cytoplasm, was high-expressed in RC tissues and cells, and that knocking down circHIPK3 could inhibit the proliferation, migration and invasion of RC cells. Previous reports revealed that circHIPK3 is highexpressed in the tissues and cells of colon carcinoma, non-small cell lung carcinoma, and nasopharyngeal carcinoma [25][26][27]. However, Li et al [28] found that circHIPK3 is significantly down-regulated in bladder carcinoma cells and is negatively related to the classification, invasion of bladder carcinoma and lymph node metastasis.…”
Section: Discussionmentioning
confidence: 96%
“…CDK6, STAT3, AKT1) ( Table 2). In addition, miR-637 could be itself regulated by non-coding endogenous competitors other than solely circHIPK3, as described in other diseases (26)(27)(28)(29)(30)(31)(32)(33)(34) (Table 2).…”
Section: A Comprehensive Analysis Of Circ-0000284 (Circhipk3) In Ccamentioning
confidence: 93%
“…We previously confirmed that microRNA-637 (miR-637) is a favorable prognosis marker in glioma that targets the 3ʹ-untranslated region (UTR) of Akt1 (13). Further targets of miR-637, such as signal transducer and activator of transcription 3 (STAT3) and nuclear protein 1 (NUPR1) (14,15), have been validated so far, but there remains a lack of knowledge regarding upstream regulation.…”
Section: Introductionmentioning
confidence: 94%